Prospect of Online Ojek (GOJEK) on Employment in Makassar City - Rostini, Rostini; Rahman, Abdul; Haris, Abdul; Rawi, Rais Dera Pua; Kahar, Muhammad Syahrul (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to know whether the development of online ojek (Gojek) effect on employment in Makassar city ". This study uses a quantitative approach. A quantitative approach emphasizes the analysis of numerical data (numbers) are processed with statistical methods. This study uses two variables: the independent variable (X) development of online ojek, and the dependent variable (Y) employment opportunity. For data analysis using simple linear regulation analysis, namely: y = a + bx; then the correlation analysis by looking at the correlation coefficient between the development of online ojek (Gojek) to employment opportunities and to measure the relationship between employment opportunity (y) with the development of online ojek (Gojek) (x), used a simple linear regression formula is used. The result of this research is that the prospect of online ojek (Gojek) in Makassar City has a profound, significant influence on employment opportunities in Makassar city, where the test results obtained correlation values between the two variables of 0.8177 means included in the category of very strong correlations, the coefficient of determination ( R ^ 2) amounted to 0.6687 which means that the magnitude of the influence exerted by the development of online ojek (Gojek) on employment opportunities in Makassar city was 6.6%.